(untitled) (Texas Journal of Medical Science, 2025)
Fetal lung maturity is a key determinant of neonatal survival and postnatal respiratory adaptation. Accurate assessment of fetal lung tissue viability plays a critical role in perinatal management, particularly in highrisk pregnancies. Doppler ultrasound has emerged as a non-invasive and highly informative tool for evaluating fetal pulmonary circulation and perfusion, offering insight into the functional development of the lungs. This study aims to evaluate the clinical significance, methodology, and diagnostic accuracy of Doppler ultrasound screening in the assessment of fetal lung tissue viability, and to provide a basis for its use in prenatal care protocols.